Rosiglitazone treatment alleviates inflammation and improves liver function in overweight women with polycystic ovary syndrome: a randomized placebo-controlled study - Rautio, Katrina; Tapanainen, Juha S; Ruokonen, Aimo; Morin-Papunen, Laure C (Fertility and sterility, 2007)
In a randomized, placebo-controlled study, we studied the effects of 4 months' treatment with rosiglitazone on low-grade inflammation, liver function, lipid levels, and blood pressure in 30 overweight women with polycystic ovary syndrome. Rosiglitazone significantly decreased serum C-reactive protein levels, white blood cell count, and alanine aminotransferase enzyme activity but did not affect lipid or blood pressure levels. Placebo had no effect on any parameters.